2017
DOI: 10.14744/anatoljcardiol.2017.7581
|View full text |Cite
|
Sign up to set email alerts
|

Tp-e interval and Tp-e/QTc ratio as novel surrogate markers for prediction of ventricular arrhythmic events in hypertrophic cardiomyopathy

Abstract: Objective:Hypertrophic cardiomyopathy (HCM) as a common genetic heart disease characterized by ventricular hypertrophy and myocardial fibrosis is significantly associated with a higher risk of fatal ventricular arrhythmic events (VAEs). We aimed to assess the interval between the peak and the end of the electrocardiographic T wave (Tp–e) and Tp–e/corrected QT (QTc) ratio as candidate markers of ventricular arrhythmias in patients with HCM.Methods:In this single-center, prospective study, a total of 66 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 26 publications
(34 reference statements)
1
25
0
Order By: Relevance
“…Furthermore, in patients with ventricular arrhythmic event (VAE) in the HCM group, the Tp‐e interval and Tp‐e/QTc ratio were significantly higher than patients without VAE and there was a positive correlation with the maximum LVWT and Tp‐e interval and Tp‐e/QTc ratio. In addition, multivariate analysis revealed that these markers were associated with a higher risk of VAE (respectively, OR: 1.060; % 95 CI: 1.005–1.117; p = 0.012 and OR: 1.148; % 95 CI: 1.086–1.204; p = 0.049) (Akboğa et al, ). In Shimizu et al study with 47 HCM patients, they found higher Tp‐e intervals compared to patients without SCD and VT.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, in patients with ventricular arrhythmic event (VAE) in the HCM group, the Tp‐e interval and Tp‐e/QTc ratio were significantly higher than patients without VAE and there was a positive correlation with the maximum LVWT and Tp‐e interval and Tp‐e/QTc ratio. In addition, multivariate analysis revealed that these markers were associated with a higher risk of VAE (respectively, OR: 1.060; % 95 CI: 1.005–1.117; p = 0.012 and OR: 1.148; % 95 CI: 1.086–1.204; p = 0.049) (Akboğa et al, ). In Shimizu et al study with 47 HCM patients, they found higher Tp‐e intervals compared to patients without SCD and VT.…”
Section: Discussionmentioning
confidence: 94%
“…Other important indices like QT, QTc, Tp-Te/QT, Tp-Te/QTc, Tp-Tec/QTc didn’t show any significant difference between groups. When looking into results more precisely in tables, our mean Tp-Te/ QT and Tp-Te/ QTc values in all groups were found higher than important cutoff levels in some trials [8], [24], [31], [32], [34]. But after careful examination, some indices were found meaningful higher than accepted cutoff points according to some trials, mean Tp-Te/QT level in our HFmrEF patients was higher than patients with BS.…”
Section: Discussionmentioning
confidence: 97%
“…They found a cutoff value of Tp-Te ≥ 77 ms and Tp-Te/QT ratio of ≥ 0.205 for predicting cardiac events with a good sensitivity and specificity level [33]. In hypertrophic cardiomyopathy patients with VA events, mean Tp-Te interval and Tp-Te/QTc ratio were longer than without events and control group (Tp-Te: 82.6 ± 9.8 ms vs. 74.6 ± 9.3 ms; Tp-Te/QTc: 0.202 ± 0 vs.0.181 ± 0; P < 0.001 for all) [34]. Another trial which included acute ST-elevation myocardial patients with coronary interventional therapy showed pre-coronary intervention (pre-CI) Tp-Te was prolonged in patients that died during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that increased Tp-Te interval is a risk factor for unsustainable ventricular tachycardia in patients with hypertrophic cardiomyopathy [24]. The latest study by Akbog et al [25] in 2017 Found thatTp-Te interval and Tp-Te / QT can be independent predictors of ventricular arrhythmias in HCM patients. A study by Chinese experts on hypertrophic cardiomyopathy (Tp-Te) confirmed that The Tp-Te interval was significantly shortened after chemoablation.…”
Section: The Hypertrophic Cardiomyopathymentioning
confidence: 97%